Interactive Evidence-Based Pressure Injury Education Program for Hospice Nursing: A Quality Improvement Approach. Issue 5 (September 2022) - Seton, Jacinta M.; Hovan, Holly M.; Bogie, Kath M.; Murray, Maudie M.; Wasil, Bridgette; Banks, Patricia G.; Burant, Christopher J.; Miller, Charman; Vogt, Marjorie
Abstract : PURPOSE: The purpose of this quality improvement (QI) project was to develop and implement an interactive, evidence-based pressure injury (PI) education program and evaluate the impact on frontline hospice nursing staff knowledge and practice. PARTICIPANTS AND SETTING: The QI setting was a 12-bed inpatient hospice unit in a tertiary care Veterans Affairs (VA) Medical Center in Cleveland, Ohio. Nineteen licensed and unlicensed hospice nursing staff participated in this pre-/postworkshop project. APPROACH: Chart audit determined baseline PI incidence and prevalence on the inpatient hospice unit. Interviews with key leaders informed the need to develop and implement innovative PI education opportunities. A literature review determined existing standards regarding the benefits of PI education for nursing staff but did not reveal measurable targets in hospice settings. We developed a PI education intervention based on Kolcaba's Theory of Comfort framework and a Plan-Do-Study-Act (PDSA) performance improvement model. Education was delivered in 7 workshops, lasting 2 hours each. Knowledge, practice, and comfort for inpatient hospice nursing staff were evaluated at baseline and 8 weeks following the final refresher visit. Workshop satisfaction was collected once using standard program evaluation forms after final workshop delivery. OUTCOMES: We observed a significant improvement in staff PI knowledge ( P = .001) and practice ( P = .001) after initial workshop attendance and repeat engagement ( P = .001). There was a large magnitude of effect for overall knowledge change ( d = 1.04); similarly PI care planning and practice showed a large magnitude of effect and significant improvement ( P = .001, d = 2.64). Staff comfort with job duties was stable with low effect size (mean 4.52, d = 0.04), and satisfaction with the workshop education was high (100% agreement with trainer effectiveness). IMPLICATIONS FOR PRACTICE: We found that frontline hospice nursing staff knowledge and practice improved after attendance at our evidence-based PI education program. Results of this QI project have stimulated ongoing discussion on how to sustain this program in our hospice setting.